Antioxidant activity in selected fresh fruits - Karunasiri, M.G.A.N.; Ravimannan, N. (University of Jaffna, 2018)
Fruits are rich in antioxidants which help in lowering incidence of degenerative diseases such as cancer, arthritis, heart disease, inflammation and acceleration of the ageing process. It is very important point to move to conventional fruits because the fruits which are highlighted as good antioxidant sources are very expensive. This study was carried out to determine the antioxidant activity (AC) in the formulation which was proposed by Brand Williams, and it is based on the inhibition of the free radical 2, 2-diphenyl-1-picrilhydrazil (DPPH) in ethanol extract of the samples. According to the results water melon (Citrullus lanatus) got the highest EC50 value (16.381± 0.698mg/ml) while star fruit (Averrhoa carambola), got the lowest EC50 value (0.073± 0.011mg/ ml) among these selected fruits. It means that water melon (C. lanatus) has the lowest antioxidant activity while star fruit (A. carambola) has the highest antioxidant activity among these selected fruits. None of the samples showed more or less similar EC50 for standard L-Ascorbic acid (0.005±0.001mg/mL). Among these selected vegetables, star fruit (A. carambola) and bilin (Averrhoa bilimbi) are not significantly different from standard sample that was L-Ascorbic acid. Except these two fruits, all the other selected fruit samples significantly differ from L-Ascorbic acid. avocado (Persea americana) significantly differs from the other fruit samples. So, that EC50 value is reducing significantly (p<0.05) as water melon (C. lanatus) 16.381± 0.698mg/mL > banana (Musa) 4.308± 0.265mg/mL > papaya (Carica papaya) 4.290±0.388mg/mL > pineapple (Ananas comosus) 1.942±0.052mg/mL > egg fruit (Pouteria campechiana) 1.712±0.030mg/mL > mango (Mangifera indica) 1.180±0.128mg/mL > duriyan (Durio sp.) 1.157±0.112mg/mL > avacado (Persea americana) 0.795±0.083mg/mL > bilin (A. bilimbi) 0.095±0.011mg/mL > star fruit (A. carambola) 0.073±0.011mg/mL. Conversely DPPH antioxidant activity increased significantly in ascending order. Considering these results, the local fruits also contain high antioxidant activities.
Keywords: Antioxidants; DPPH method; EC50 value; Fruits; Radicals